Changes in absolute theta power in bipolar patients during a saccadic attention task. Issue 3 (30th August 2015) - Cartier, Consuelo; Diniz, Claudia; Di Girogio, Luiza; Bittencourt, Juliana; Gongora, Mariana; Ken Tanaka, Guaraci; Teixeira, Silmar; Basile, Luis F.; Novis, Fernanda; Angélica Silveira, Luciana; da Silva, Rafael de Assis; Cagy, Mauricio; et al.
Abstract: The present study analyzed absolute theta power (ATP) in brain areas involved with attention in the three phase of BD while the patients performing a saccadic attention task. We hypothesized that patients in depression and mania states show a higher ATP compared to euthymic patients, since a higher ATP is indicative of attention deficit. We analyzed the frontal (F7, F3, F z, F4 and F8) and central (C3, Cz and C4) areas. Thirty bipolar patients were enrolled in this study. The subjects performed a saccadic attention task while their brain activity pattern was recorded using quantitative electroencephalography (20 channels). Our results showed a main effect for group over C3, C4, Cz, F7, F4, F8 electrodes, and a main effect for moment over Cz, F7, F8 electrodes. These results indicate that both task and groups produce changes in theta activity in distinct cortical areas that participate in the organization of attention. Our results therefore demonstrate that, although it is well established in the literature that theta has a relevant role in the attention process, it is necessary to deepen the investigations to better understand the specifics of theta during visual processing tasks that have a demand for attention. Highlights: Theta activity differentiates Bipolar Disorder Phases. Theta activity participates in the organization of attention. Bipolar Disorder presents attention deficit.